A Review of Classical and Modern Control Techniques Utilized in Modern Microgrids - Shahbaz, Muhammad H.; Amin, Arslan Ahmed (Recent Advances in Electrical & Electronic Engineering, 2021)
Because of the consistently expanding demand of energy, the introduction of a decentralized microgrid based on energy resources will soon be the most exciting development in the power system. Microgrids (MGs), which are mainly based on inverters, are becoming more popular as they can handle different forms of renewable energy effectively. However, one of the most challenging areas of research is their control. In the last few years, many control strategies have been developed. In this review, different control methods have been discussed, applicable to the MG system. Furthermore, the comparative analysis of classical and modern control strategies is also considered. This survey guides the new researchers about all available control strategies and room for improvement towards the optimal solution of the MG control techniques. It also identifies several research gaps and future trends therein as well as provides a solution to manage problems in MGs. The strategies are then compared based on their applicability to different control requirements.
Keywords: neural networks